2017
DOI: 10.1038/nature23262
|View full text |Cite
|
Sign up to set email alerts
|

Maternal H3K27me3 controls DNA methylation-independent imprinting

Abstract: Mammalian sperm and oocytes have different epigenetic landscapes and are organized in different fashions. After fertilization, the initially distinct parental epigenomes become largely equalized with the exception of certain loci, including imprinting control regions. How parental chromatin becomes equalized and how imprinting control regions escape from this reprogramming is largely unknown. Here we profile parental allele-specific DNase I hypersensitive sites in mouse zygotes and morula embryos, and investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
398
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(446 citation statements)
references
References 53 publications
16
398
3
1
Order By: Relevance
“…Interestingly, the knockdown of KDM6B in SCNT embryos leads to a moderate increase in the expression of KDM6A, consistent with our previous findings in mouse parthenogenetic embryos [41]. While our paper was under preparation, another study reported the identification of H3K27me3-dependent imprinting genes (which include Gab1, Sfmbt2, and Slc38a4), and previous studies have shown that these genes exhibit a loss of imprinting in SCNT embryos [57,58]. This provides an explanation for why the knockdown of the H3K27me3 demethylase KDM6B promotes SCNT efficiency.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the knockdown of KDM6B in SCNT embryos leads to a moderate increase in the expression of KDM6A, consistent with our previous findings in mouse parthenogenetic embryos [41]. While our paper was under preparation, another study reported the identification of H3K27me3-dependent imprinting genes (which include Gab1, Sfmbt2, and Slc38a4), and previous studies have shown that these genes exhibit a loss of imprinting in SCNT embryos [57,58]. This provides an explanation for why the knockdown of the H3K27me3 demethylase KDM6B promotes SCNT efficiency.…”
Section: Discussionsupporting
confidence: 91%
“…This complex is recruited to and silences specific regions of the genome by transferring methyl groups onto lysine 27 of histone H3. This chromatin modification has well-defined roles in the maintenance of the stem cell state and genomic imprinting (Juan et al, 2016; Inoue et al, 2017). Collectively, these observations indicate that oxygen concentrations have a strong influence on the control of chromatin modifying enzymes and significantly impact the regulation of two crucial pluripotency-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of chromatin structure in germ cells is pivotal as these cells are the bridge between generations and therefore potential vector of epigenetic information. In particular, H3K27me3 has been shown to be involved in parental imprinting 21,22,23 . Yet, in contrast to the extensive characterization of PRC2 in models such as mouse embryonic stem cells (ESC), much less is known about the regulation of its enzymatic activity in germ cells.…”
Section: Theirmentioning
confidence: 99%